DEVELOPING A MODELING ALGORITHM FOR HYDRAULIC PROCESSES AND WATER QUALITY IN WATER SUPPLY SYSTEMS (International Conference on Economics, Finance, Banking and Management, 2025)
In this article, the issues of comprehensive modeling of hydraulic processes and water quality dynamics for the efficient management of water supply systems under modern conditions are examined. The main objective of the study is to develop an integrated hydraulic–chemical modeling algorithm that accounts for real-time flow velocity, pressure, reservoir level, concentrations of reactive substances, and the propagation of tracer compounds. The article analyzes hydraulic processes using the EPANET 2.2 software environment and models pressure losses across pipe diameters, variations in flow velocity, flow distribution at nodes, and the temporal dynamics of water quality indicators (residual chlorine, turbidity, and tracer concentration) based on the operational data of the Nurafshon city water supply network.